Faster approximation algorithm for generalized maximum concurrent flow problem with budget constraint - Dong, Liwei; Liying Bian; Tang, Hengyong (2008 IEEE International Conference on Service Operations and Logistics, and Informatics, 2008)
We present fully polynomial approximation algorithm for generalized maximum concurrent flow problem with budget constraint that run in time independent of the number of commodities k. We show that by modifying the algorithms by Karakostas and Fleischer. We can reduce their running time. At the same time the approximation solution of the new algorithm is closer to optimal value.